Revealing the Prevalence of Echinococcus Granulosus in Kirkuk City by Serological and Molecular Methods - Shakour, Sunbul Jalal (American Journal of Biology and Natural Sciences, 2025)
The Echinococcus granulosus species complex is the source of the neglected parasite disease known as cystic echinococcosis (CE), which is found all over the world. Clinical and molecular epidemiological studies from endemic regions with little data, like the Middle East, are especially needed to better understand the paths of transmission of this parasite. The study’s objectives were to determine the sociodemographic characteristics of the patients and the COX1 gene of the E. granulosus complex in Kirkuk, Iraqi people. Human blood samples (350), and hydatid cyst materials (HCF and germinal layer) were obtained from 20 HCs patients after surgical removal of the cysts and aspiration of the cyst fluid by sterile 20ml disposable syringe, in Kirkuk and Azadi teaching hospitals at October 2024 to February 2025. The results showed that out of 350 blood samples taken from patients for the purpose of detecting E. granulosus infection using the ELISA technique with anti-hydatid cyst antibodies (IgG), 27 (7.7%) were found to be positive. The findings found that females had the highest percentage, reaching 5.4%, while the percentage of males was 2.3%. As for age, the age group 35-44 was the highest, reaching 11 (40.7%) out of a total of 27 positive samples, while the lowest age group was 15-24 years, reaching (14.8%) out of a total of 27 positive samples. Also, it was found that rural had the highest percentage, reaching 85.2%, while the percentage of urban was 14.8%. finally, the results showed the partial mt DNA of COX1 gene of all of the 20 samples that isolated from human were successfully amplified using conventional PCR, the expected band 443bps product were detected on 1.5% agarose gel after staining with Redsafe. Figure (1) showed the partial mt DNA of COX1 gene of all of the 17 samples that isolated from human were successfully amplified using conventional PCR, the expected band 443bps product were detected on 1.5% agarose gel after staining with Redsafe. It is concluded that the incidence of E. granulosus infection is related to sociodemographic factors. Furthermore, the COX1 gene may be considered a good indicator for detecting E. granulosus.